2014
DOI: 10.18632/oncotarget.1899
|View full text |Cite
|
Sign up to set email alerts
|

SIAH2 antagonizes TYK2-STAT3 signaling in lung carcinoma cells

Abstract: The Janus tyrosine kinases JAK1-3 and tyrosine kinase-2 (TYK2) are frequently hyperactivated in tumors. In lung cancers JAK1 and JAK2 induce oncogenic signaling through STAT3. A putative role of TYK2 in these tumors has not been reported. Here, we show a previously not recognized TYK2-STAT3 signaling node in lung cancer cells. We reveal that the E3 ubiquitin ligase seven-in-absentia-2 (SIAH2) accelerates the proteasomal degradation of TYK2. This mechanism consequently suppresses the activation of STAT3. In agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…It should be highlighted that the previous study did not use any prior stimulation with IFNβ, which could potentially contribute to the observed differences between the two screens. The ubiquitin ligase SIAH, identified in our study as a negative regulator, was previously shown to degrade TYK225. The re-identification of previously known regulators of IFN-I signaling SIAH2 and TRIM9 in our screen confirm that the approach we undertook was reliable.…”
Section: Discussionsupporting
confidence: 69%
“…It should be highlighted that the previous study did not use any prior stimulation with IFNβ, which could potentially contribute to the observed differences between the two screens. The ubiquitin ligase SIAH, identified in our study as a negative regulator, was previously shown to degrade TYK225. The re-identification of previously known regulators of IFN-I signaling SIAH2 and TRIM9 in our screen confirm that the approach we undertook was reliable.…”
Section: Discussionsupporting
confidence: 69%
“…The protein expression of Siah2 reportedly correlates with clinicopathologic factors and poor prognosis in various cancers, such as breast cancer, 11,12 prostate cancer, 13,14 lung cancer, 15,16 pancreatic cancer, 17 liver cancer, 18 oral cancer, 19 and melanoma. 20,21 However, the role of Siah2 expression in gynecological cancers remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Siah2 has been described as a proto-oncogene. 7,10 Increasing evidence revealed that Siah2 promotes the progression of various malignant tumors, such as breast cancer, 11,12 prostate cancer, 13,14 lung cancer, 15,16 pancreatic cancer, 17 liver cancer, 18 oral cancer, 19 and melanoma. 20,21 However, the prognostic value of Siah2 expression in EOC remains unknown.…”
mentioning
confidence: 99%
“…The expression of SIAH2 can increase due to gene copy number duplications in the more aggressive TNBC type [33]. This mechanism has also been suggested for lung squamous cell carcinomas [11]. In Japanese hormone-receptor-positive (HRP) female breast cancer patients (1086 patients and 1816 female controls), a significant association of the disease with an intronic SNP in SIAH2 was reported [65].…”
Section: Expression Of Siahs In Breast Tumors and Potential Prognostimentioning
confidence: 91%
“…While both, SIAH1 and SIAH2 are inducible by the tumor suppressor and transcription factor p53, sex hormones and cytokine signaling only contribute to the regulation of SIAH2 [10][11][12][13][14][15][16][17] (Fig. 1; please note: details are discussed in Section 3).…”
mentioning
confidence: 99%